2017
DOI: 10.1111/oik.04266
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dispersal mode on the environmental and spatial correlates of nestedness and species turnover in pond communities

Abstract: Advances in metacommunity theory have made a significant contribution to understanding the drivers of variation in biological communities. However, there has been limited empirical research exploring the expression of metacommunity theory for two fundamental components of beta diversity: nestedness and species turnover. In this paper, we examine the influence of local environmental and a range of spatial variables (hydrological connectivity, proximity and overall spatial structure) on total beta diversity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
101
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(124 citation statements)
references
References 53 publications
19
101
1
3
Order By: Relevance
“…, Hill et al. ). Although this process may be important to explain β‐diversity patterns at biogeographical scale, where nestedness may reflect the extinction/colonization dynamics resulting from past glaciations (Dobrovolski et al.…”
Section: Discussionmentioning
confidence: 99%
“…, Hill et al. ). Although this process may be important to explain β‐diversity patterns at biogeographical scale, where nestedness may reflect the extinction/colonization dynamics resulting from past glaciations (Dobrovolski et al.…”
Section: Discussionmentioning
confidence: 99%
“…The small catchment areas of ponds (Williams et al 2003) and the different management practices promotes a wide range of successional stages and environmental conditions across urban areas for macroinvertebrate taxa to utilise (Hill et al 2015;Thornhill et al 2017a). Previous studies have demonstrated that variation in local environmental conditions are often the principle regulator of species turnover in pond systems as macroinvertebrate taxa are essentially filtered by environmental gradients (Cottenie 2005;Hill et al 2017b). Compositional differences driven by species turnover may also reflect the isolation of some ponds within urban settlements, which may increase the level of ecological uniqueness of urban ponds Fahrig 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, high beta-diversity among urban ponds in this study was dominated by species turnover (species replacement from one pond to another) rather than nestedness indicating that pond conservation practices (individual sites of high diversity) are not providing the most effective conservation of pond biodiversity. The dominance of species turnover suggests that conservation actions to enhance pond biodiversity would be most beneficial if undertaken at a landscape/network scale, conserving an array of complementary sites (incorporating the 'principle of complementarity'; Justus and Sarkar Landscape Ecol (2018) 33:389-405 401 2002) with different species compositions (Hill et al 2017b). Current pond conservation strategies need to be adapted in recognition of the fact that the greatest conservation value of ponds lies at the network scale reflecting the high contribution of species turnover to beta-diversity, in the heterogeneity of conditions among sites (promoting high community turnover and heterogeneity); and that conservation efforts should be focussed to ensure that pondscapes and heterogeneous environmental conditions at a landscape scale are maintained and where possible enhanced.…”
Section: Conservation Implicationsmentioning
confidence: 99%
“…The highest levels of diversity in river floodplain systems are often observed at intermediate levels of LHC (Gallardo et al, 2014;Turić et al, 2015;Ward & Tockner, 2001). Active dispersing invertebrates might show in stronger responses to local environmental variables, indicating the importance of species sorting and habitat filtering, and a weaker response to LHC, whereas passive dispersing invertebrates might respond stronger to LHC (Dube et al, 2017;Hill, Heino, Thornhill, Ryves, & Wood, 2017;Li et al, 2019). Active dispersing invertebrates might show in stronger responses to local environmental variables, indicating the importance of species sorting and habitat filtering, and a weaker response to LHC, whereas passive dispersing invertebrates might respond stronger to LHC (Dube et al, 2017;Hill, Heino, Thornhill, Ryves, & Wood, 2017;Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%